Impact of Life Events upon Onset of Depression Disorder In AL-Diwanyia Governorate : A Case-Control Study - jabor, Haider; AL-Juboor, ali (Iraqi National Journal of Nursing Specialties, 2012)
Objective: The aim of this study is to find out the impact of life events upon onset of depression, to describe the prevalence of life events among depressed patients. Methodology: Retrospective a case-control study conducted in AL-Diwanyia Teaching Hospital, Psychiatric Department on A non-probability (purposive sample) of (60) depressed patients and (60) of healthy person were matched with them from general population. The data were collected through the use of semi-structured interview by questionnaire, which consists of two parts (1) divide, section A. cover letter and B. Sociodemographic data which consists of 9-items, (2) Life events questionnaire consists of 51-items distributed to six dimensions include, family and social dimension, financial dimension, work and school dimension, legal and criminal dimension, health dimension and change of residency dimension. Results: The findings of the present study indicate that the depressed patients have more exposed to life events than control group before one year of onset of depression, family and social dimension, financial dimension, legal and criminal dimension more effect on depression onset. Recommendations: The study recommends that increase the individual, family and community awareness about stress management to decrease the impact of life events upon their health.